The Effect of Planting Media Composition on the Growth of Dendrobium Sp. Orchid Seedlings - Nur Rokhimah Hanik; Ratna Dewi Eskundari; Tri Wiharti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Fern is the best growing medium for orchids, because it is protected, a solution is needed to find a substitute for fern media. In this study, a combination of stem charcoal, husk charcoal and peanut shell compost was chosen. The combination of the three was chosen because the charcoal sticks and husk charcoal are relatively sterile and the peanut shell compost can function as a medium and fertilizer. The purpose of this study 1. To determine the effect of the composition of the planting medium on the growth of Dendrobium sp orchid seeds 2. To determine the best composition of the growing media for the growth of Dendrobium sp orchid seeds. The research time was 2.5 months, the object of the research was the Dendrobium sp. orchid aged 12 months, the research location was at Paranet's house, Gabahan Village, RT 05 RW 12, Jombor Sukoharjo. Simple randomized study design with 4 treatments. Treatment A Planting orchid seeds with a mixture of ferns and peanut shell compost in 10 pots. Treatment B was planting orchid seeds with a mixture of stem charcoal, husk charcoal, and peanut shell compost in a ratio of 1:1:1 for 10 pots. Treatment C was planting orchid seeds with a mixture of charcoal stems, husk charcoal and peanut shell compost in a ratio of 1/4:1/4:1/2 for 10 pots. Treatment D was planting orchid seedlings. The variables observed were the number of leaves, leaf length, leaf area, number of tillers, and wet weight measured 12 weeks after treatment. Data analysis using Varieties Test (Anova or Kruskal Wallis Test) followed by Duncan's Multiple Range Test (DMRT) or Mood Median Test. Growth parameters were observed (leaf length, number of leaves, leaf area, and wet weight). As for the number of tillers, there was a difference in influence, although the difference was not significant. Treatment The combination of K.1/2 media or with a comparison of peanut shell compost, charcoal stems and husk charcoal 1/2:1/4:1/4 gave the best effect on the 4 observed growth parameters (Leaf Length, Leaf Number, Leaf Area). , and wet weight). From the results of this study, collectors, orchid lovers and orchid entrepreneurs can use a combination of stem charcoal, husk charcoal and peanut shell compost as a substitute for ferns with a mixture of charcoal stems, husk charcoal, and peanut shell compost in a ratio of 3/8:3/ 8:2/8.